2022
DOI: 10.3390/buildings12060791
|View full text |Cite
|
Sign up to set email alerts
|

Window-Windcatcher for Enhanced Thermal Comfort, Natural Ventilation and Reduced COVID-19 Transmission

Abstract: We investigate and test the effectiveness of a novel window windcatcher device (WWC), as a means of improving natural ventilation in buildings. Using ANSYS CFX, the performance of the window-windcatcher is compared to a control case (no window-windcatcher), in three different geographic locations (Cardiff, Doha and Amman) which are representative of three different types of atmospheric conditions. The proposed window-windcatcher has been shown to improve both thermal comfort and indoor air quality by increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…The aims and objectives of this paper are to quantify the effect of air conditioning (AC) temperature setpoint on the energy consumption and CO 2 emissions of a generic ASHRAE-based residential building. The model studied herein has been developed in DesignBuilder using a set of essential parameters, including building layout, which is shown in Figure 1 [27,28]. In addition, the parameters include the building design specifications, which include the construction materials (to define insulation and predict heat transfer) [27,28], the HVAC systems [12,23], the lighting system [12,23], and the activity templets [12,23]).…”
Section: Numerical Model Specifications and Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aims and objectives of this paper are to quantify the effect of air conditioning (AC) temperature setpoint on the energy consumption and CO 2 emissions of a generic ASHRAE-based residential building. The model studied herein has been developed in DesignBuilder using a set of essential parameters, including building layout, which is shown in Figure 1 [27,28]. In addition, the parameters include the building design specifications, which include the construction materials (to define insulation and predict heat transfer) [27,28], the HVAC systems [12,23], the lighting system [12,23], and the activity templets [12,23]).…”
Section: Numerical Model Specifications and Assumptionsmentioning
confidence: 99%
“…The model studied herein has been developed in DesignBuilder using a set of essential parameters, including building layout, which is shown in Figure 1 [27,28]. In addition, the parameters include the building design specifications, which include the construction materials (to define insulation and predict heat transfer) [27,28], the HVAC systems [12,23], the lighting system [12,23], and the activity templets [12,23]). These parameters are specified in Tables 1 and 2.…”
Section: Numerical Model Specifications and Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Additionally, compared to other apertures, windcatchers have a larger pressure coefficient (Cp), which allows for greater ventilation rates. 23 In fact, a wind tunnel test 24 found that windcatchers performed better in terms of Cp than other openings. In areas without access to windows, like basements, windcatchers can be especially useful.…”
Section: Introductionmentioning
confidence: 99%